2014
DOI: 10.1021/ja510183c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanodots: Toward a Comprehensive Understanding of Their Photoluminescence

Abstract: We report the characterization of carbon nanodots (CNDs) synthesized under mild and controlled conditions, that is, in a microwave reactor. The CNDs thus synthesized exhibit homogeneous and narrowly dispersed optical properties. They are thus well suited as a testbed for studies of the photophysics of carbon-based nanoscopic emitters. In addition to steady-state investigations, time-correlated single-photon counting, fluorescence up-conversion, and transient pump probe absorption spectroscopy were used to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
391
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(415 citation statements)
references
References 35 publications
15
391
4
5
Order By: Relevance
“…[21,[24][25][26][27][28] Thec harge-transfer activity of CNDs has recently been explored, both in ground and excited states, [27,29] for the excited states this was done in conjunction with av ariety of electron donors and acceptors. [26,30] Fori nstance,C NDs have been used together with complementary forms of nanocarbons,s uch as fullerenes,c arbon nanotubes,g raphene,i n tailored charge-transfer systems.Inaleading example,CNDs have been combined with single-walled carbon nanotubes (SWCNTs) affording supramolecular nanohybrids,i nw hich the components function as electron donors and acceptors. [31] Graphene-oxide/CND and methylviologen/CND nanohybrids-brought together by electrostatic interactions-have also been found to feature remarkable charge-transfer activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,[24][25][26][27][28] Thec harge-transfer activity of CNDs has recently been explored, both in ground and excited states, [27,29] for the excited states this was done in conjunction with av ariety of electron donors and acceptors. [26,30] Fori nstance,C NDs have been used together with complementary forms of nanocarbons,s uch as fullerenes,c arbon nanotubes,g raphene,i n tailored charge-transfer systems.Inaleading example,CNDs have been combined with single-walled carbon nanotubes (SWCNTs) affording supramolecular nanohybrids,i nw hich the components function as electron donors and acceptors. [31] Graphene-oxide/CND and methylviologen/CND nanohybrids-brought together by electrostatic interactions-have also been found to feature remarkable charge-transfer activity.…”
Section: Introductionmentioning
confidence: 99%
“…[27,30] We recently reported an ovel synthetic approach that gives uniform approximately 1nmC NDs. [26] Moreover,w e demonstrated that CNDs form stable charge-transfer hybrids with either electron donors or acceptors.The mutual electron donor-acceptor interactions can be fine-tuned using electrostatic interactions with the negatively charged edge groups of CNDs.F urthermore,t he central units of the CND layers feature extended p-systems,w hich is susceptible for pstacking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A much more pronounced polydispersity is found for the CND1 and CND2 compared to the predominantly UV-absorbing pCND studied previously. 16 Moreover, a slight bimodality is present for CND1 and CND2. ) for several hours.…”
Section: Conceptual Insightsmentioning
confidence: 97%
“…[12][13][14][15] We have seen that CNDs are prone to undergo photoinduced charge-transfer in nanohybrid materials, indicating that they are also suitable as photoactive components. [16][17][18] Indeed, several studies have shown that the principle of using such materials as sensitizers in mesoscopic solar cells is sound, although the reported power conversion efficiencies cannot yet compete with inorganic QD solar cells. [19][20][21][22][23][24] We here classify GQDs as structurally well-defined, carbonrich organic molecules that generally require multi-step synthetic procedures in contrast to CNDs, which are usually synthesized in a single step but do not exhibit a well-defined molecular structure.…”
Section: Conceptual Insightsmentioning
confidence: 99%
See 1 more Smart Citation